Detection of extracellular enzymes of fungal pathogen associated with pineapples rot disease / Muhammad Muqseed Mamut - Mamut, Muhammad Muqseed (Faculty of Plantation and Agrotechnology, 2018)
This study investigates the type of enzymes produced by a fungus that involved in the pathogenesis of pineapple rot disease. Based on isolation and identification, two types of fungus pathogen were identified which is Fusarium spp, and Colletotrichum spp while one biological agent were identified as Trichoderma spp. Three type of enzymes were screened which are protease, amylase, and lipase as these are main enzymes produced by the fungus during invasion and colonization of plant host. Therefore, three enzymatic test was conducted which are proteolytic activity, amylolytic activity, and lipolytic activity. The test showed that Fusarium spp. produced all type of enzymes such as protease, lipase, and amylase. However, Trichoderma spp. produced only one enzyme which is protease and lastly, Colletotrichum spp. produced two enzymes namely protease and amylase. As a conclusion, the most important pathogen is Fusarium spp. as they could produce three types of a different enzyme to colonize and kill the crop.